ส่วนประสมการตลาดที่มีผลต่อผู้บริโภคเจนเนอเรชั่นวายในอำเภอเมืองเชียงใหม่ต่อการซื้อเครื่องสำอางบำรุงผิวหน้า นำเข้า - ทัศนียาภรณ์ สัตย์มาก (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This study aimed to review marketing mix affecting generation Y consumers in Mueang Chiang Mai district towards purchasing imported facial skin cares. Samples of this study were determined to 300 generation Y consumers in Mueang Chiang Mai district, composing of 150 males and 150 females, who purchased imported facial skin cares within the last 6 months. Questionnaires were used as the tool to collect data. Data were, then, analyzed by the descriptive statistics, consisting of frequency, percentage and mean, and One way ANOVA, including T-Test and F-Test. The findings showed that most respondents were in the age between 24-27 years old with Bachelor’s degree and single. Their monthly income was 10,001-25,000 Baht. They worked as employee or officer at the private company. The results of the study on consumer behavior towards purchasing imported skin cares presented that recently, the imported skin care that the majority applied was found in the cleansing or foaming facial cleanser category of L’OREAL brand. The main reason of purchasing imported facial skin cares was the need of white and radiant facial complexion. Person influencing their decision towards purchasing the imported skin cares was the respondents themselves. They purchased the product at the time when the existing one was almost finished / finished and preferred to continue purchasing the same product brand since they trusted in its quality. For those who did not purchase the product in the same brand as before, their reason was given to the preference of trying on new products. They frequently purchased the imported facial skincare products from the cosmetic shop and were not in favors of purchasing a full set of products (in the same brand) being applied in every step of facial treatment. For those who purchased the full set of product (in the same brand), they believe that it would strengthen product effectiveness in rejuvenating facial skin. For those who were not in favors of purchasing the full set of product (in the same brand), they thought that some types of products were not necessary. Most of them averagely spent 1,001-3,000 Baht per month for the imported facial skin cares. Source of information where they learned about the studied products was television. The findings on marketing mix factors revealed that the following factors affected purchasing decision of the respondents at high level: price, promotion, product and place, respectively. In Product factor, the top three elements affecting decision of the respondents towards purchasing imported facial skin cares were product safety with non-allergenic and non-irritation, simple direction, and clear information of expiration dates, accordingly. In Price factor, the top three elements affecting decision of the respondents towards purchasing imported facial skin cares the most were reasonable price comparing to product quality, clear product price tag, and reasonable price comparing to product quantity, accordingly. In place factor, the top three elements affecting decision of the respondents towards purchasing imported facial skin cares the most were accessible procurement, convenient distribution place near to their homes, and product availability at general department stores, supermarkets or hypermarket, and etc., accordingly. In promotion factor, the top three elements affecting decision of the respondents towards purchasing imported facial skin cares the most were product discount, availability of product trials prior to purchase, and personality and reliability of salesperson as well as product review (as found in equal means), accordingly.